2021
DOI: 10.5137/1019-5149.jtn.33661-21.3
|View full text |Cite
|
Sign up to set email alerts
|

The importance of multiple gene analysis for diagnosis and differential diagnosis in charcot marie tooth disease

Abstract: AIM: Charcot-Marie-Tooth (CMT) disease or hereditary motor and sensory neuropathy (HMSN) is the definition of a genetically heterogeneous group of diseases characterized by the impaired function of peripheral nerves. The aim of this study was to investigate the genetic etiology of CMT. MATERIAL and METHODS:We herein examined 55 non-related patients with a suspicion of CMT phenotype or HMSN using a customized multigene panel based on the next-generation sequencing technique. All cases were previously analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To date, genetic spectrum studies of IPNs have been completed and updated in several countries [ 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. We have reviewed these reports and compared them with our findings in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic spectrum studies of IPNs have been completed and updated in several countries [ 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. We have reviewed these reports and compared them with our findings in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients were offered an annual follow-up evaluation for VUS. In different CMT-NGS studies, various results were reported for VUS according to population diversities [16][17][18] . Larger population-based studies could reduce the prevalence of VUS.…”
Section: Gnb4 Litaf Mfn2mentioning
confidence: 99%
“…This results in the loss of regulatory activity on HSPB2, which eventually causes aberrant nuclear foci formation (Morelli et al, 2017b). Finally, from the analysis of a small cohort of CMT/dHMN patients, a novel variant of unknown significance, the HSPB3 L6F, has been recently identified in a patient affected by dHMNII (Yalcintepe et al, 2021). To our knowledge, animal models of HSPB3 mutants have not been developed.…”
Section: Hspb3mentioning
confidence: 99%